2008
DOI: 10.1002/cyto.a.20541
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Plasmodium falciparum growth and development by UV flow cytometry using an optimized Hoechst‐thiazole orange staining strategy

Abstract: The complex life cycle of Plasmodium falciparum (Pf) makes it difficult to limit infections and reduce the risk of severe malaria. Improved understanding of Pf blood-stage growth and development would provide new opportunities to evaluate and interfere with successful completion of the parasite's life cycle. Cultured blood stage Pf was incubated with Hoechst 33342 (HO) and thiazole orange (TO) to stain DNA and total nucleic acids, respectively. Correlated HO and TO fluorescence emissions were then measured by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 66 publications
4
81
0
Order By: Relevance
“…In practice, detection of ring stages with non-GFP-fluorescent lines may require the application of an alternative staining method such as the combination of thiazole orange and hydroethidine (44) or Hoechst 33342 and (45). Previous studies have reported an encouraging correlation between flow cytometry and microscopy counts of drug-treated cultures in vitro (45,46) as well as application of flow cytometry to assess drug inhibition of late-stage parasite development (47). In this study, the correlation between numbers of free merozoites and parasite growth inhibition (newly invaded rings) has been described in detail.…”
Section: Discussionmentioning
confidence: 99%
“…In practice, detection of ring stages with non-GFP-fluorescent lines may require the application of an alternative staining method such as the combination of thiazole orange and hydroethidine (44) or Hoechst 33342 and (45). Previous studies have reported an encouraging correlation between flow cytometry and microscopy counts of drug-treated cultures in vitro (45,46) as well as application of flow cytometry to assess drug inhibition of late-stage parasite development (47). In this study, the correlation between numbers of free merozoites and parasite growth inhibition (newly invaded rings) has been described in detail.…”
Section: Discussionmentioning
confidence: 99%
“…However, since individual developmental stages generate different amounts of singlet oxygen highly synchronized plasmodial stages are a prerequisite for flow cytometry applications. Alternatively counterstaining with different fluorescent dyes could be applied to enable specific visualization of infected and noninfected erythrocytes as well as different developmental stages of the malaria parasite (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…For RNA and DNA staining (46), rbcs were pelleted and resuspended in 400 μl of Retic-COUNT Reagent (thiazole orange [TO]; BD), and then HO 34580 added at a 4-mM final concentration. A total of 100,000 cells were collected by the LSRFortessa flow cytometer, and data were analyzed by FACSDiva software.…”
Section: Methodsmentioning
confidence: 99%